2003
DOI: 10.1104/pp.102.017913
|View full text |Cite
|
Sign up to set email alerts
|

AtSig5 Is an Essential Nucleus-Encoded Arabidopsis σ-Like Factor

Abstract: Transcription of chloroplast genes is subject to control by nucleus-encoded proteins. The chloroplast-encoded RNA polymerase (PEP) is a eubacterial-type RNA polymerase that is presumed to assemble with nucleus-encoded -factors mediating promoter recognition. Recently, families of -factor genes have been identified in several plants including Arabidopsis. One of these genes, Arabidopsis SIG5, encodes a -factor, AtSig5, which is phylogenetically distinct from the other family members. To investigate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…The heterozygous mutant (+/SIG5-3), but not homozygous mutant, was obtained and displayed a white shriveled ovule phenotype (Fig. 6 B, a), which is similar to the phenotype reported earlier with +/sig5-1 and +/sig5-2 (26). Further analysis of the mutant showed that when normal ovules developed to the early globular embryo stage, a fraction of sig5 ovules, like some in +/ank6 plants, were arrested at the FG1 stage (Fig.…”
Section: Ank6 Interacts With Mitochondrial/plastid Transcription Initsupporting
confidence: 73%
See 4 more Smart Citations
“…The heterozygous mutant (+/SIG5-3), but not homozygous mutant, was obtained and displayed a white shriveled ovule phenotype (Fig. 6 B, a), which is similar to the phenotype reported earlier with +/sig5-1 and +/sig5-2 (26). Further analysis of the mutant showed that when normal ovules developed to the early globular embryo stage, a fraction of sig5 ovules, like some in +/ank6 plants, were arrested at the FG1 stage (Fig.…”
Section: Ank6 Interacts With Mitochondrial/plastid Transcription Initsupporting
confidence: 73%
“…3B). SIG5 is a member of the σ-factor family of proteins that function as transcription initiation factors in both chloroplasts and mitochondria (26). Interestingly, disruption of SIG5 function was reported to cause homozygous lethality similar to the phenotype of ank6 observed here.…”
Section: Ank6 Interacts With Mitochondrial/plastid Transcription Initmentioning
confidence: 71%
See 3 more Smart Citations